Framework for optimal energy storage duration for maximum-reliability renewable electricity - Sadhukhan, Jhuma; Sen, Sohum; Randriamahefasoa, T. M. S. (Frontiers in Energy Research, 2024)
Energy system optimization is needed for optimum sustainable net-zero electricity (NZE) mix even for regional/local scales because of the energy storage needs to address renewable energy supply intermittency.This study shows a novel regional/local energy planning model for optimum sustainable net-zero electricity (NZE) mix under spatiotemporal climate/meteorological and electrical load demand constraints. A generic robust non-linear constrained mathematical programming (NLP) algorithm has been developed for energy system optimization. It minimizes levelized cost and greenhouse gas emissions while maximizing reliability against stored energy discharge analysis (RADA). Reliability is the ratio between excess stored renewable power discharge and unmet load demand, a measure of the extent of unmet load demand met by excess stored renewable power. Coupled with the NLP, the RADA and energy storage evaluations determine the seasonal energy storage (SES) conditions and realistic renewable proportions for NZE. The significance of the framework lies in determining the maximum hours of viable electrical energy storage beyond which the reliability enhancement is infinitesimal. Significant observations include 96 hours of maximum viable electrical energy storage beyond which the reliability enhancement is infinitesimal. While this observation is robust based on previous reporting for the case of the USA, a realistic NZE mix for the UK South is observed as follows. Direct wind and solar can meet 63%, 62%, and 55% of electricity demand in South West, Greater London, and South East, UK. Further, battery energy storage systems can increase the renewable proportion by 21%, 22% and 13%, respectively. The unmet demands can be met by renewable electricity through SES. Compressed air energy storage (CAES) and pumped hydro offer viable SES. Thereafter, natural gas with carbon capture and storage (CCS), bioenergy and hydrogen SES are the choices in the increasing order of costs per lifecycle climate impact potential, to meet the electricity demand.